2016
DOI: 10.1080/00396265.2016.1263179
|View full text |Cite
|
Sign up to set email alerts
|

Triple-frequency GNSS models for PPP with float ambiguity estimation: performance comparison using GPS

Abstract: He obtained his B.App.Sc and M.Sc degrees in 1998 and 2010, respectively. His current research focus is on precise point positioning with multi-constellation and multi-frequency GNSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…It was shown that triple-frequency combinations could improve the PPP convergence time and the precision of the estimated parameters by about 10%. Deo and El-Mowafy (2016) presented three triple-frequency PPP models, namely, the triple-frequency code-only and phase-only ionosphere-free model, the mixed code and phase model and the individual uncombined model. By comparison with the traditional dual-frequency model, it was shown that all three triple-frequency models had improved the convergence time (CT) required to achieve and maintain a 3D positional accuracy of 5 cm, by 8%-11%.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that triple-frequency combinations could improve the PPP convergence time and the precision of the estimated parameters by about 10%. Deo and El-Mowafy (2016) presented three triple-frequency PPP models, namely, the triple-frequency code-only and phase-only ionosphere-free model, the mixed code and phase model and the individual uncombined model. By comparison with the traditional dual-frequency model, it was shown that all three triple-frequency models had improved the convergence time (CT) required to achieve and maintain a 3D positional accuracy of 5 cm, by 8%-11%.…”
Section: Introductionmentioning
confidence: 99%
“…where λ c and N c represent the IF wavelength and the corresponding ambiguity, respectively. However, the modeling of triple-frequency PPP using two dependent IF linear combinations needs to account for the correlations between observations [21,22]. Moreover, the observation noise is increased for both code and phase observations.…”
Section: Functional Modelmentioning
confidence: 99%
“…Since the float-ambiguity PPP is a positioning method that is characterised by a long initialisation period for convergence of the solution and ambiguities (Deo and El-Mowafy, 2017), two cases were considered to evaluate the impact of using the predicted clocks and IGU orbits. The first case represents a typical scenario, where a break in communications and in receiving the real-time corrections is assumed taking place during normal PPP operation, e.g.…”
Section: The Impact Of Prediction On Ppp Solution Convergencementioning
confidence: 99%